MERS-CoV antibodies in humans, Africa, 2013–2014 - Liljander, Anne M.; Meyer, B.; Jores, Joerg; Müller, M.A.; Lattwein, E.; Njeru, I.; Bett, Bernard K.; Drosten, C.; Corman, V.M. (Centers for Disease Control and Prevention, 2016)
Dromedaries in Africa and elsewhere carry the Middle East respiratory syndrome coronavirus (MERS-CoV). To search for evidence of autochthonous MERS-CoV infection in humans, we tested archived serum from livestock handlers in Kenya for MERS-CoV antibodies. Serologic evidence of infection was confirmed for 2 persons sampled in 2013 and 2014.